THE INCIDENCE OF MALIGNANCY IN MULTINODULAR GOITER. - Shahida Baloch1, Sajjad Hussain Qureshi2, Kashif Ali Shah3, Shahnawaz Laghari4, Naeem Bhatti5, Maimona khushk6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
INTRODUCTION: Thyroid cancer is the rare one but it the most frequently occurring malignancy among all endocrine glands carcinomas. It can present as solitary nodule and a dominant nodule in multinodular goiter (MNG). In Pakistan, its incidence is 1.2% cases of all neoplastic lesions and studies have summed up that 57% to 89% of carcinomas are papillary type. In globe, its incidence varies from 7.5% to 13%. There is a minor statistical difference seen in incidence of multi nodular and solitary nodular goiter. OBJECTIVE OF STUDY: The objective of this study was to detect the prevalence of thyroid neoplasm in multinodular goiter. STUDY DESIGN: Cross sectional study. PLACE AND DURATION OF STUDY: At Surgical Unit-II PMC Hospital Nawabshah. Duration was from January 2020 to December 2020. PATIENTS AND METHODS: All the patients with diagnosis of MNG were admitted through OPD and emergency department. Clinical History and thorough clinical examination of neck was done. All biochemical investigations were done Fine Needle Aspiration Cytology (FNAC) was obtained. Thyroid Profile was done in all patients and thyroid scan were done wherever deemed necessary. Surgery was done and specimen was sent for histopathology to diagnose Carcinoma. RESULTS: Total 92 patients with diagnosed as MNG were included in the study. Female patients were 60(65%) and male patients were 32 (35%). On Fine needle Aspiration Cytology (FNAC), 31(34%) patients had malignant cells and 61(66%) had benign cells. After surgeries performed, histopathologies of specimen of patients were done. Of them papillary carcinoma was reported in 26(28.2%) patients, 3(3.2%) were diagnosed as medullary, 2 (2.1%) as follicular and no nay case of anaplastic was found in our study. Colloid goiter was found among 41(44.5%) patients and 20(21.7%) patients had follicular adenoma. CONCLUSION: In short, it is concluded that the prevalence of thyroid carcinoma in MNG is higher that is 34%.